2009
DOI: 10.1021/am900167r
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Sensing Behavior of Polydiacetylene Liposomes Embedded in Alginate Fibers

Abstract: Polydiacetylene (PDA)-doped calcium alginate fibers were created by the solution blending of polymerized 10,12-pentacosadiynoic acid liposomes with sodium alginate in water prior to extrusion. The liposomes maintained their blue color during wet spinning and drying of the fibers but changed to red with exposure to specific external stimuli (heat, solvent, and chemical). In the latter case, the color change only occurred when the fibers were sufficiently permeable for the reacting species to reach the interior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…4,[7][8][9][10][11][12][13][14] Most PDAs appear with an intense blue color related to an absorption maximum at a wavelength l max of around 640 nm. External stimuli such as temperature, [7][8][9][10][11][12][13]15 pH, 16,17 stress, 18 ions, 19 solvents, 20 ligands, 21 and biomaterials cause a color change to the red phase with l max around 550 nm. 22 The intriguing stimuli-responsive color change properties [23][24][25] show potential for applications in sensing.…”
Section: Introductionmentioning
confidence: 99%
“…4,[7][8][9][10][11][12][13][14] Most PDAs appear with an intense blue color related to an absorption maximum at a wavelength l max of around 640 nm. External stimuli such as temperature, [7][8][9][10][11][12][13]15 pH, 16,17 stress, 18 ions, 19 solvents, 20 ligands, 21 and biomaterials cause a color change to the red phase with l max around 550 nm. 22 The intriguing stimuli-responsive color change properties [23][24][25] show potential for applications in sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Polydiacetylenes (PDAs) are unique linear π‐electron‐conjugated polymers derived from the topochemical polymerization of the corresponding diacetylene monomers, by a solid‐state polymerization on exposure to UV, X‐ray, γ‐ray, or electron beams . PDAs have attracted great interest due to their electronic and optical properties, for many unique applications, especially in light‐emitting diodes (OLEDs) and sensors . In fact, PDAs are potential sensing materials because of their ability to undergo color change in response to various external stimuli such as temperature, pH, solvent, and host–guest interactions …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] PDAs have attracted great interest due to their electronic and optical properties, for many unique applications, especially in light-emitting diodes (OLEDs) [ 4,5 ] and sensors. [6][7][8][9] In fact, PDAs are potential sensing materials because of their ability to undergo color change in response to various external stimuli such as temperature, [10][11][12] pH, [ 10,13 ] solvent, [ 14 ] and host-guest interactions. [15][16][17] It was reported that the preparation of PDAs by photo chemical polymerization requires the imbalance of electronic density distribution and assembly of diacetylene monomers in an appropriate arrangement to favor 1,4-addition polymerization.…”
mentioning
confidence: 99%
“…Hauschild et al (2005) used different lipids to form lipid vesicles with the ink-jet printing method and reported 100 nm and 130 nm in diameter. Kauffman et al (2009) reported a bimodal particle distribution with largest particle size of 144 ± 22 nm in diameter using a more traditional sonication method. Sonication is a much cruder process compared to the inkjet method.…”
Section: Characterization Of Pda Vesiclesmentioning
confidence: 99%